Approaches to teaching Dante's divine comedy - Kleinhenz, Christopher; Olson, Kristina (New York : Modern Language Association of America, 2020)
"Offers pedagogical techniques for teaching Dante's Divine Comedy. Includes considerations of textual traditions, translations, the work's relation to classical works, gender and LGBTQ themes, visual arts, music, popular culture, theology, video games, the papacy, and influence. Gives syllabus suggestions for high school, undergraduate, graduate, and creative writing courses, and prison settings"--
Includes bibliographical references (pages 271-300).
Keywords: Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321 -- Study and teaching; Epic poetry, Italian -- Study and teaching